A new implementation of chaotic S-boxes in CAPTCHA. Issue 2 (February 2016) - Khan, Majid; Shah, Tariq; Batool, Syeda
Abstract A Completely Automated Public Turing test to tell Computers and Humans Apart (CAPTCHA) is a program that can generate and grade tests that humans can pass but current computer programs cannot. The humans can read distorted text as the one shown below, but current computer programs cannot. We have proposed a novel chaos-based CAPTCHA. We have utilized our proposed S-box and used chaotic iterative relation to select a completely random CAPTCHA for the security of web portal and other user interface multimedia where human interaction with the machine is verified.